Floral development of the Ornithocephalus clade (Oncidiinae, Orchidaceae): The origin of the tabula infrastigmatica, gynostemium appendices and labellar callus - Royer, Carla A; Toscano De Brito, A. L. V; Stützel, Thomas; Smidt, Eric C; Nunes, Elaine L. P (Oxford University Press (OUP), 2021)
The Ornithocephalus clade comprises small epiphytes distributed in 12 genera and c. 120 species. Their flowers have complex structures, the homologies of which are difficult to interpret. Through ontogenetic studies, we identified the origins of the tabula infrastigmatica, floral appendages located in the gynostemium and the labellar callus. Using a scanning electron microscope (SEM), we analysed flowers at various developmental stages from representatives of three genera: Ornithocephalus (two species), Phymatidium (two species) and Zygostates (three species). The tabula infrastigmatica of Phymatidium results from the fusion of the lateral carpels and staminodes, with different degrees of synorganization across species and can be considered a plesiomorphic characteristic within the clade. Contradicting hypotheses of a staminodial origin, the auricles present in this genus derive from the gynostemium. In Zygostates, the lateral appendices derive from staminodes and can show different development degrees, whereas in Ornithocephaus that character has been lost. We corroborate the view that the labellum is a single organ derived from the median petal and the labellar callus is derived from it.
Keywords: floral ontogeny; gynostemium; homology; lateral carpels; staminodes